UNSUR-UNSUR PAKELIRAN GAYA YOGYAKARTA DALAM PAKELIRAN NARTOSABDO - Sudarko Sudarko (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2010)
The title of this paper is â€œElements of Puppet Show (Pakeliran) Yogyakarta Style in Nartosabdoâ€™s Puppet Showâ€. Election of Nartosabdoâ€™s pakeliran as an object of this paper is based on his popularity in the puppetry world that can affect later followed by young puppeteers. The issues discussed are: (1) Effect of pakeliran Yogyakarta style elements to the Nartosabdoâ€™s pakeliran. (2) The causes Nartosabdoâ€™s pakeliran influenced by the pakeliran Yogyakarta style. The rationale used was that the puppetry art is one of tradition art that is always changing all the time. The change is dependent on human beings. Nartosabdo is a creative puppeteer artist who also makes changes in his pakeliran, among which he included elements of pakeliran Yogyakarta style in his pakeliran. The method used is descriptive interpretative, while data collection techniques by literature study and listening to sound recordings.Key words:Â Pakeliran (puppet show), Nartosabdo, Yogyakarta